LEISURE EXPERIENCE DIMENSIONS: A STUDY ON PARTICIPANTS OF ANKARA FESTIVAL - Müge Akyıldız; Metin Argan (Pamukkale University, 2010)
Experience in leisure is a key area because leisure experience has become to be seen as the primary outcomes of leisure participation involving interactions with others. In this sense, the purpose of the study is to present the results of a study examining leisure participants' experiences and experiential satisfaction and recommendation intentions. The concept of leisure experience dimensions are discussed in the light of current literature followed by empirical findings on the subject matter. Results revealed three aspects, which are "feeling and think experience", "act and relate experience" and "sense experience". The results of the study suggest that these experiential dimensions of leisure have significant effects on experiential satisfaction and recommendation intentions. The study has significant implications as to how well marketing practitioners and recreationist implement experiential marketing and experiential dimensions of leisure practices.